La ética y su importancia en las relaciones laborales de los funcionarios de la Unidad Jurídica de la Gobernación de Los Ríos - Trujillo Bajaña, José Humberto (2019)
The present case study was carried out to the officials of the Legal Unit of the Government of Los Ríos in which, it allowed to know the real problem in the entity, so that ethics is the human skill to develop equanimity of a professional and thus project confidence in the work environment. In the various research activities have been kept, writing and announcing, so that different people interested in this topic such as ethics and its importance in labor relations can obtain adequate information. It is also essential to maintain a good working environment in the environment of an institution for the benefit of obtaining the stated objectives of the entity and in order to improve the affinity among officials. The link between ethics and labor relations is that employees work with responsibility, honesty, respecting the code of the establishment's standards, so that they put into practice their moral values and thus take responsibility for this research, that is why With this work we sought to emphasize the importance of the presence of ethics and determined the results found in the realization of this topic.